STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA PENGELOLA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN TLOGOMAS KOTA MALANG - Nawawi, Ahmad; Indra Gunawan , Cakti; Sasmito, Cahyo (Jurnal Paradigma Ekonomika, 2023)
Micro, small and medium enterprises are an important component for the community's economy in Tlogomas Village, Malang City. This study aims to analyze the inhibiting and supporting factors as well as the latest models in local government strategies in improving the quality of MSME management human resources. The method used in this study is descriptive qualitative, with data analysis including data reduction, data presentation, and drawing conclusions. the inhibiting factors, namely the unsynchronized implementation of HR training times, inadequate capacity of HR training locations, intense MSME competition, difficult access to capital, difficulties in adapting to changes after the Covid-19 pandemic. Supporting factors are good communication between the Cooperative and MSME Office of Malang City and MSME actors in the Tlogomas Village as well as financial assistance and incentives from the local government to MSME actors. The latest model in the strategy to improve the quality of human resources for MSME managers is the role of the government and human resources as drivers and managers of MSME operational management.